Synthesis and Antibacterial Activity of 2’-Hydrtoxy 3’-Bromo-5’-ethyl Chalcones and 3-(2’-Hydroxy-3’Bromo-5’-Ethyl Phen-1’-yl)-5-Substituted Phenyl-2-Isoxazoles - Naik, V.R.; Naik, H.B. (Asian Journal of Chemistry, 2010)
Some new 2-isoxazole derivatives have been prepared by condensation of α, β -dibromo chalcomes with hydroxylamine hydrochloride in ethanol in presence of potassium hydroxide. These varied products have been characterised by spectral studies and screened for antibacterial activity.